Review on Plant Diversity Status and Conservation Practices in Nepal - Shrestha, Sudha Joshi (Patan Pragya, 2020)
Plant diversity plays the crucial role in maintaining the ecosystem and sustaining the life in the globe. Nepal lying in central Himalaya and at the crossroad of two phytogeographicregionsisbestowed with rich biodiversity. Though the country occupies about 0.1% of global land area but comprises 3.2% of world’s known flora. Biodiversity is eroding because of many factors such as habitat loss, deforestation, infrastructure development, over exploitation for human use, invasion by alien species, global climate change and natural calamities, thus threatening the existence in globe. Nepal has adopted both in-situ and ex-situ conservation practices to conserve the biodiversity and maintain the ecosystem in nature. A network of 20 protected areas is established and national forests under different categories are under protection to conserve the biodiversity in their natural habitats. Scientific forest management was initiated to enhance the forest productivity and conserve biodiversity. Botanical gardens in different localities are established for the conservation of rare, endangered, threatened and endemic plant species. Moreover, Government of Nepal has enlisted some plant species in Government protection list and CITES appendices to prevent them from degradation. Thirty three plant species with medicinal values are prioritized for research and economic development of the nation. Nepal’s approach in conservation of plant diversity is commendable and is at the forefront in in-situ conservation practice. However, a considerable number of plants species that are rare, threatened, endemic are also found outside the protected are as and need to be conserved.